Preliminary studies in some aspects of amino acids biosynthesis in juveniles of penaeus monocon fabricus - Coloso, Relicardo M.
Some aspects of amino acid biosynthesis in Penaeus monodon Fabricus were studied. Ion-exchange chromatography in conjuction with radioisotope labelling techniques were used to investigate the incorporation of 14C from (U-14C)-acetate into amino acids of precipitable proteins in P. monodon juveniles. Highest 14C radioactivity was found in the acidic amino acids, aspartic acid and glutamic acid. Little but significant radioactivity was observed in alanine, cysteine, glycine, proline, and serine. Amino acids which incorporated little or 14C were arginine, histidine, isoleucine, leucine, lysine, methione, phenylalanine, threonine, tyrosine, and valine. It appears that P. monodon juveniles could not synthesize these amino acids from acetate. The essential nature of these amino acids in P. monodon is discussed.